2021
DOI: 10.3390/jcm10071422
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Hospital Volume of Severely Injured Patients and In-Hospital Mortality of Severely Injured Pediatric Patients in Japan: A Nationwide 5-Year Retrospective Study

Abstract: Appropriate trauma care systems, suitable for children are needed; thus, this retrospective nationwide study evaluated the correlation between the annual total hospital volume of severely injured patients and in-hospital mortality of severely injured pediatric patients (SIPP) and compared clinical parameters and outcomes per hospital between low- and high-volume hospitals. During the five-year study period, we enrolled 53,088 severely injured patients (Injury Severity Score, ≥16); 2889 (5.4%) were pediatric pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Among the studied volume-outcome associations, 18 analyses were adjusted for patient demographics and injury severity ( Table 3 ). Of the 17 studies included, 16 explored the volume’s impact on effectivity (mortality) [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], 5 on efficiency [ 10 , 13 , 15 , 20 , 23 ], 2 on safety [ 11 , 23 ], and 4 on timeliness [ 20 , 21 , 23 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the studied volume-outcome associations, 18 analyses were adjusted for patient demographics and injury severity ( Table 3 ). Of the 17 studies included, 16 explored the volume’s impact on effectivity (mortality) [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], 5 on efficiency [ 10 , 13 , 15 , 20 , 23 ], 2 on safety [ 11 , 23 ], and 4 on timeliness [ 20 , 21 , 23 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is important to provide high-quality trauma care to improve the mortality of patients with severe injuries. Several studies have reported that a higher hospital admission volumes resulted in lower mortality among severely injured patients because the increased volume of severely injured patients per hospital was correlated with an increased number of urgent procedures required for severely injured patients, such as blood transfusions, TAE and/or surgical intervention 20 21. Moreover, previous studies showed that patients with penetrating injuries had a survival benefit if they were centrally triaged to higher-level trauma centres 22.…”
Section: Discussionmentioning
confidence: 99%
“…injured patients with ISS 0-15 and 16-25 was significantly lower than that of patients with ISS �16 (0.05 and 0.22 vs 1.00, p <0.001). The ISS cutoff value of ISS �16 has been commonly used as the definition of severe injury in Japanese trauma research [10][11][12]14]. However, it may be necessary to change the definition of severe injury to include those having ISS cutoff values of �26 instead of �16, since trauma mortality trend has decreased and OR for mortality of injured patients with ISS �26 was relatively higher than those of patients with ISS 0−15 and 16−25 in the past decades.…”
Section: Plos Onementioning
confidence: 99%